HER3 Is a Determinant for Poor Prognosis in Melanoma - Reschke, Markus; Mihic-Probst, Daniela; van der Horst, Edward Htun; Knyazev, Pjotr; Wild, Peter J.; Hutterer, Markus; Meyer, Stefanie; Dummer, Reinhard; Moch, Holger; Ullrich, Axel (Clinical cancer research, 2008)
Purpose: The epidermal growth factor receptor family member HER3 is overexpressed in diverse human cancers and has been associated with poor prognosis in breast, lung, and ovarian cancer. However, the relevance of HER3 with regard to its prognostic significance and function in primary melanoma and metastases remains largely elusive. Experimental Design: HER3 protein expression was analyzed immunohistochemically using tissue microarrays of 130 primary melanoma and 87 metastases relative to established clinical variables. The possibility of an influence of HER3 on melanoma cell proliferation, migration, invasion, and chemotherapy-induced apoptosis was studied in human melanoma cell lines. Results: We show that HER3 is frequently expressed in malignant melanoma and metastases at elevated levels. High HER3 expression may serve as a prognostic marker because it correlates with cell proliferation, tumor progression, and reduced patient survival. Suppression of HER3 expression by RNA interference reduces melanoma cell proliferation, migration, and invasion in vitro . In addition, down-regulation of HER3 synergistically enhances dacarbazine-induced apoptosis. Moreover, monoclonal antibodies specific for the extracellular portion of HER3 efficiently block heregulin-induced proliferation, migration, and invasion of melanoma cell lines. Conclusion: Our results provide novel insights into the role of HER3 in melanoma and point out new possibilities for therapeutic intervention.